2005
DOI: 10.1080/0071660500066183
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding hemp seed meal to laying hens

Abstract: Seed of the hemp cultivar Unika-b was cold-pressed to obtain hemp seed meal (HSM) containing 307 g/kg crude protein and 164 g/kg ether extract (60 g/kg linoleic acid, 120 g/kg alpha-linolenic acid, 160 g/kg oleic acid, lesser amounts of palmitic, stearic, and gamma-linolenic acids). For 4 weeks, 102 43-week-old DeKalb Sigma hens were fed on isonitrogenous and isoenergetic diets containing 0, 50, 100 or 200 g/kg HSM. Eggs were collected for fatty acid analysis during the fourth week of feeding these diets. No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 13 publications
(16 reference statements)
12
59
1
Order By: Relevance
“…Contrary to the potential of industrial hempseed, its use in the poultry diet is not recommended due to a lack of scientific evidence to support nutritional efficacy (Gakhar et al, 2012). Previous reports have shown that the addition of hempseed can potentially generate n-3-enriched eggs (Silversides and Lefrançois, 2005;Gakhar et al, 2012;Neijat et al, 2015). In the present study, the results are encouraging since the profile of fatty acids improved significantly.…”
Section: Discussionmentioning
confidence: 53%
“…Contrary to the potential of industrial hempseed, its use in the poultry diet is not recommended due to a lack of scientific evidence to support nutritional efficacy (Gakhar et al, 2012). Previous reports have shown that the addition of hempseed can potentially generate n-3-enriched eggs (Silversides and Lefrançois, 2005;Gakhar et al, 2012;Neijat et al, 2015). In the present study, the results are encouraging since the profile of fatty acids improved significantly.…”
Section: Discussionmentioning
confidence: 53%
“…The inclusion of hemp seed at levels up to 14% in the diet had no detrimental effect on growth or feed efficiency of cattle compared to the control diet and as such, Gibb et al (2005) suggested that hemp seed could be a feasible high energy animal feed by-product of the hemp fibre industry. Silversides and Lefrancois (2005) offered hemp seed meal to laying hens and observed that levels up to 200 g/kg had no effect on egg production, feed intake, feed efficiency or body weight. The inclusion of hemp seed meal altered the fatty acid profile of egg yolks, with levels of ALA significantly (P b 0.05) greater than with the control diet (0.2 g/100 g total FA), being 0.5, 0.7 and 1.2 g/100 g total FA for diets containing 50, 100 and 200 g hemp seed meal/kg diet respectively.…”
Section: Hempmentioning
confidence: 97%
“…Feeding cold-pressed hempseed products as a protein feed instead of soybean meal has resulted in similar production results in poultry and fish (Hullar et al, 1999;Callaway, 2004;Silversides & Lefrançois, 2005). Despite the potential of hempseed in livestock production, only a few studies on hempseed products as a protein feed for ruminants have been undertaken (Mustafa et al, 1999;Gibb et al, 2005).…”
Section: Introductionmentioning
confidence: 95%